Implementation of the Principle of Good Faith in Contract Performance - Irfansyah, Muhammad Fajar; Darmawan, Didit; Hardyansah, Rommy (Bulletin of Science, Technology and Society, 2024)
The principle of good faith is a fundamental principle in treaty law that plays an important role in ensuring fair and ethical implementation of contracts. This research aims to examine the application of the principle of good faith in the implementation of agreements using a legal literature approach. The background of this research is based on the existence of default cases arising from violations of the principle of good faith, thus creating legal uncertainty in the settlement of contract disputes. With a focus on Indonesian civil law regulations and international practices, this research explores the effectiveness of the principle of good faith in overcoming complex legal issues in contract implementation. The results show that the application of the principle of good faith in Indonesia still faces challenges in the form of a lack of clear definitions and operational guidelines. This study highlights the importance of integrating the principle of good faith in the pre-contractual stage up to dispute resolution to create substantive justice in contractual relationships. The study concludes with a recommendation to develop a more structured guideline for the implementation of the principle of good faith to reduce potential disputes and increase the parties' confidence in the execution of contracts.